Research on social anxiety disorder continues to escalate: A commentary on Asmundson and Asmundson's analysis of publication trends in the anxiety disorders. (May 2018) - Heimberg, Richard G.; Butler, Rachel M.
Highlights: Research on social anxiety disorder (SAD) increased substantially from 1980–2005 to 2006–2016. Empathy for persons with SAD, maybe driven by evolutionary factors, may help explain this increase. The high prevalence of SAD and its comorbidity with other disorders may be contributing factors. The availability of theoretical models of SAD and its treatment is an important factor. Changes over time in DSM definitions have broadened the conception of SAD and its importance. Abstract: Asmundson and Asmundson (2018) reported that publication of research on anxiety disorders, including social anxiety disorder (SAD), has seen rapid growth in the period between 2006 and 2016. In fact, the uptick in publication rate of SAD research was unexpectedly high given previous predictions by Boschen (2008), who reviewed publication trends from 1980 to 2005. In this commentary, we consider potential factors involved in the continued increase in publication of research on SAD. We examine the roles that empathy and evolutionary factors may play in our ability to relate to those with SAD and in our motivation to research it. Further, we consider whether the relatively high prevalence of SAD, the visibility of experiences of social anxiety in the general population, and the availability of viable theoretical models of SAD and its treatment have played a significant role in the high publication rate. Other factors affecting research on SAD such as changes in the definition of SAD in various editions of the Diagnostic and Statistical Manual of Mental Disorders (DSM), comorbidity which other psychiatric disorders, and the role of pharmaceutical company research are also discussed.